2018
DOI: 10.1016/j.biopha.2018.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic acid ameliorates bleomycin-induced lung fibrosis in rats

Abstract: The present results showed the ability of SA to restore the antioxidant system and to inhibit oxidative stress, proinflammatory cytokines, extracellular matrix, and TGF-β. This is first report demonstrating that SA amoleriates BLM induced lung injuries through inhibition of apoptosis and induction of Nrf2 and HO-1 mediated antioxidant enzyme via NF-κB inhibition. The histopathological finding reveals that SA treatment (10 and 20 mg/kg) significantly ameliorates BLM induced lung injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 61 publications
11
27
1
Order By: Relevance
“…Therefore, SA and CAP appear to possess potent anti-inflammatory effects. Our data corroborates with our previous studies, where SA was found to be an inhibitor of oxidative stress and inflammatory cytokines [12,48]. Moreover, NF-κB p65 activation may lead to DOX-induced apoptosis in the myocardium [49].…”
supporting
confidence: 92%
“…Therefore, SA and CAP appear to possess potent anti-inflammatory effects. Our data corroborates with our previous studies, where SA was found to be an inhibitor of oxidative stress and inflammatory cytokines [12,48]. Moreover, NF-κB p65 activation may lead to DOX-induced apoptosis in the myocardium [49].…”
supporting
confidence: 92%
“…Natural herbs and their phytoconstituents with potent antioxidant, anti-inflammatory, and antiapoptotic effects may offer good gastrointestinal protection. Sinapic acid (SA) has potent antioxidant, anti-inflammatory, and antiapoptotic activities (Raish et al, 2018a;Bin Jardan et al, 2020). The current article reports the first in vivo study of the gastroprotective effects of SA and the underlying mechanism of gastric protection in ethanol-induced GUs in rats.…”
Section: Introductionmentioning
confidence: 99%
“…SA is considered a natural antioxidant [1012]. In vivo study has shown that oral administration of SA increases expression of Nrf2 and HO-1 in kidney, lung, and colon tissues in rats [13, 14]. SA has also been shown to inhibit the IL-1 β -induced production of inducible nitric oxide synthase (iNOS), nitric oxide (NO), prostaglandin E2 (PGE2), and cyclooxygenase (Cox)-2 in rat chondrocytes [15].…”
Section: Introductionmentioning
confidence: 99%